2005
DOI: 10.1051/0004-6361:20042214
|View full text |Cite
|
Sign up to set email alerts
|

Inference of the magnetic field in spicules from spectropolarimetry of He I D$_\mathsf{3}$

Abstract: Abstract. We present observations of spicules in the He  D 3 line with full-Stokes spectropolarimetry, which were done with the Advanced Stokes Polarimeter at the Dunn Solar Telescope of the Sacramento Peak Observatory. The line profiles appear to be significantly broadened by non-thermal processes, which we interpret using the hypothesis of a distribution of velocities inside the spicule. The possibility of inferring the magnetic field in those conditions is tested on synthetic data, and the results are gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 15 publications
2
26
0
Order By: Relevance
“…Such a distance off-limb corresponds to the low spicular region, as proven by the broadening of the spectral features in Ba ii (when compared to on-disk profiles, as seen in the following figures of this paper, the central peak broadens almost 10%, from a Gaussian fit with FWHM of 110 mÅ on disk to 123 mÅ off disk). This broadening is characteristic of spicules (Krat & Krat 1971;López Ariste & Casini 2005;Trujillo Bueno et al 2005) and is considered as non-thermal in nature. The polarization pattern in Fig.…”
Section: Stokes Q Profilesmentioning
confidence: 99%
“…Such a distance off-limb corresponds to the low spicular region, as proven by the broadening of the spectral features in Ba ii (when compared to on-disk profiles, as seen in the following figures of this paper, the central peak broadens almost 10%, from a Gaussian fit with FWHM of 110 mÅ on disk to 123 mÅ off disk). This broadening is characteristic of spicules (Krat & Krat 1971;López Ariste & Casini 2005;Trujillo Bueno et al 2005) and is considered as non-thermal in nature. The polarization pattern in Fig.…”
Section: Stokes Q Profilesmentioning
confidence: 99%
“…Levens et al (2016) investigated the magnetic field in and around prominence bubbles finding increases in the inferred magnetic field strength in these regions, which the authors interpret as being consistent with the bubble being formed by emerging magnetic flux. This is the first attempt at such measurements and aspects of the results support the ideas behind bubble formation, but cautions has to be taken due to the relatively large space of parameters where solutions to the inversions exist (López Ariste and Casini 2005).…”
Section: Prominence Bubblesmentioning
confidence: 83%
“…They point out, however, that significantly stronger fields could also be present (as indicated by larger Stokes-V signals detected during another observing run). The possibility of magnetic fields significantly larger than 10 G was also tentatively suggested by the He I D 3 measurements of López Ariste & Casini (2005), although these spicules emanated from active plage. More detailed spectropolarimetric observations of spicules in the He I D 3 multiplet were carried out by Ramelli et al (2006), who found B≈10 G in quiet Sun and B≈50 G in more active areas.…”
Section: Introductionmentioning
confidence: 64%